AN IN-DEPTH STUDY OF STATE’S ETHICAL OBLIGATION UNDER INTERNATIONAL LAW - Jain, Anshu; Kalgotra, Upasana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
At international level, all States are governed through certain set of norms and rules which are mutually agreed by them in the form of international law. These rules play a significant role in the maintenance of peace and security among all the nations. But the leading aspect of this research paper shall be the implementation of international law by the State parties. It is very important to understand the nature of international law before binding its compliance over the States. Few jurists have viewed it as a perfect law while other group of jurists consider it as not a law at law due to the lack of three organs of the government. Moreover, the advocates of this thought view this law based on moral norms. Hence, the researcher has made a wide study over the concept of law and morality with the help of famous jurists. International law has been further explained in terms of natural law where States are made to conform to international law without any external force. Obligation towards international law is imbibed inside human nature through natural law. States does not require to sign any treaty for complying international law. However, it has been observed that States follow international law for their self-interest while placing other State’s interest at stake. States does not feel bound towards the implementation of international law in their respective legal system.